Pengembangan E-LKPD Berbasis Problem Based Learning Menggunakan Book Creator Di Kelas V Sekolah Dasar - Putri Fauziah Yazmin; Risda Amini (Elementary Teacher Education Program, Majalengka University, 2023)
LKPD in elementary schools are usually in the form of questions that must be answered by students. This causes students to be lazy to reveal the concept of material that supports learning, so that this results in the achievement of learning objectives. E-LKPD is a form of learning aid that introduces technology to students, in accordance with the 2013 curriculum, learning must utilize available technology and be in accordance with the characteristics of students. Therefore this study raises the title regarding the development of E-LKPD. Research on the development of E-LKPD uses the R&D (Research and Development) approach using the ADDIE method (Dick & Carry, 1996). The development of this E-LKPD uses a Problem Based Learning Book Creator application. This study aims to develop a valid and practical Problem Based Learning E-LKPD in grade V SD. The results of the validation test obtained from this study amounted to 95.07% with a very valid category from 3 aspects namely, material aspects, language, and media aspects. For the practicality test the results obtained were 93.4% with (very practical category).